Arms trade: a global epidemic - Nanthikesan, Suppiramaniam (1999)
Suppiramaniam Nanthikesan argues that collective violence is fast becoming a global health burden and that prevention of violence should be incorporated into the policy agendas of health communities around the world. He illustrates how trade in conventional arms is a legitimate and important arena for intervention by policy makers concerned with health. - Reproduced
Keywords: Public health; Health services